The Response to Asymmetrical Violence in Black Space - Stephanie D. Jones (Social Sciences)
Oakland, California has been identified as a Black city since the early days of the Great Migration. Migrants from the South brought their labor, families, and most importantly, a vision for the future of Black communities. Alongside the influx of domestic Black folks moving into the city has been a steady stream of Black immigrants who help to push the boundaries for how Blackness is understood in Oakland. Increased anti-immigrant sentiments have added to this violence, putting undocumented immigrants at risk of suffering the abuses of landlords. In this article, I uplift the voices of Oakland community members that demonstrate the tragedies of dispossession as they tell their own geographic stories. These collective stories demonstrate the markers of dispossession on different levels as the sociospatial dynamics of Oakland are being (re)imagined. Oakland has now become one more example of the threat to Black spaces in the U.S. and gives us a roadmap for how these spaces will be reimagined under asymmetrical violence.